Development of body adiposity in children and adolescents from Rzeszow, and its variability over 35 years - Perenc, Lidia; Radochońska, Anna; Błajda, Joanna (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Level and type of body adiposity is a positive measure of health condition. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Purpose of the study. Assessment of development of adiposity in children and adolescents of both sexes, aged 4–18, and its changes in the period of 35 years. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The total of 1563 children from Rzeszów were examined in 2013/2014. Measurements were carried out to examine thickness of three skinfolds: above triceps brachii muscle, in the umbilical area, and below the scapula; based on that whole body adiposity was calculated. The findings were subjected to statistical analyses. The results were compared with the data collected previously, in: 1978/79, 1993/1994, 2003/2004. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Up until early school age there is stable increase in the skinfold thickness. Starting with the age of 11–12 years subjects of both sexes are found with significantly higher growth in triceps skinfold thickness and greater total body adiposity. In the boys of this age group the phenomenon is observed in the umbilical skinfold, and in the girls in the subscapular skinfold. At the age from 14 to 15, the boys are found with higher rate of growth in subscapular skinfold and the girls in umbilical skinfold. Besides the growth, adiposity has also been found to decrease. During puberty standard deviations assume the highest values. Longitudinal analysis of the data for the period from 1978/79 to 2013/14 shows increasing adiposity in boys and girls and the trend is observed in all the examined skinfolds. Subjects of both genders in the relevant period of 35 years are found with continued increase in whole body adiposity, yet during the most recent decade the trend has been inhibited. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. 1. Development of adiposity in children and adolescents from Rzeszow differs between the sexes, and is highly variable during puberty. 2. Up until early school age development of adiposity tends to be gradual, and then it is found not only to significantly increase but also to decrease (adiposity fluctuation). 3. It can be concluded that during the relevant period of 35 years body adiposity in both sexes tends to accelerate, yet during the most recent decade the trend has been inhibited.